CD49a Identifies Polyfunctional Memory CD8 T Cell Subsets that Persist in the Lungs After Influenza Infection - Reilly, Emma C.; Sportiello, Mike; Emo, Kris Lambert; Amitrano, Andrea M.; Jha, Rakshanda; Kumar, Ashwin B. R.; Laniewski, Nathan G.; Yang, Hongmei; Kim, Minsoo; Topham, David J. (Frontiers in Immunology, 2021)
CD8 T cell memory offers critical antiviral protection, even in the absence of neutralizing antibodies. The paradigm is that CD8 T cell memory within the lung tissue consists of a mix of circulating TEM cells and non-circulating TRM cells. However, based on our analysis, the heterogeneity within the tissue is much higher, identifying TCM, TEM, TRM, and a multitude of populations which do not perfectly fit these classifications. Further interrogation of the populations shows that TRM cells that express CD49a, both with and without CD103, have increased and diverse effector potential compared with CD49a negative populations. These populations function as a one-man band, displaying antiviral activity, chemokine production, release of GM-CSF, and the ability to kill specific targets in vitro with delayed kinetics compared with effector CD8 T cells. Together, this study establishes that CD49a defines multiple polyfunctional CD8 memory subsets after clearance of influenza infection, which act to eliminate virus in the absence of direct killing, recruit and mature innate immune cells, and destroy infected cells if the virus persists.